2016
DOI: 10.1080/01691864.2016.1192063
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of general triglide parallel manipulators

Abstract: Optimization design of parallel manipulators has attracted much interest from researchers in recent years. The reported methodologies attempted to achieve optimal design of parallel manipulators considering several properties, such as dexterity, stiffness, and space utilization, which are important parameters to be considered. However, stiffness analysis considered by many researchers generally ignores the deformation of the mobile platform. For space utilization, there is no reported method to consider the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Equation (14) gives two solutions for z. z must be negative, because the moving platform must move under the fixed base, so the solution of z is:…”
Section: Forward Position Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (14) gives two solutions for z. z must be negative, because the moving platform must move under the fixed base, so the solution of z is:…”
Section: Forward Position Kinematicsmentioning
confidence: 99%
“…To address the problems of high nonlinearity, low accuracy and low robustness in LDRs, numerous control strategies have been proposed. Dongtao [14] determined the kinematic reliability and sensitivity of LDRs. Fu et al [15] designed an LDR with three arms and showed that problems with kinematic accuracy are mostly due to U joint errors, clearances and driving errors.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are studies about the matrix relationship between the robot's kinematics and dynamics that have been established, about dynamic simulations of the robot, the synthesis of parallel manipulators, the robot's direct dynamics and inverse dynamics, and robot optimization. A few studies on the real-time control of the Star par-allel robot exist [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%